Euro Crisis and plurality: Does the political orientation of newspapers determine the selection and spin of information?. (August 2016) - Salgado, Susana; Nienstedt, Heinz-Werner
This article studies the impact of right and left moderate political orientation of newspapers on the levels of plurality in the news coverage of the Euro Crisis in 20 newspapers from 10 European countries through a methodology based on Simpson's D index. The expectation of finding distinct patterns of coverage leading to high levels of plurality was not fully supported and the results have shown that national frames influence levels of overall plurality more than political ideology.